Circulating follicle stimulating hormone levels influence body growth in pre-menarcheal girls in a latitude-dependent manner. Issue 4 (April 2023) - Khalid, Amna; Qaisar, Rizwan; Hussain, M. Azhar; Karim, Asima
Abstract: Introduction: Age at menarche is an essential determinant of reproductive life of a woman. Latitude is an important driver of age at menarche, however the contributions of circulating follicle stimulating hormone (FSH) and socio-economic status (SES) to age at menarche in a latitude-dependent manner is not known. Methods: This population-based cross-sectional study is a component of our major cohort of 10, 050 schoolgirls aged 8–16 years from 35 schools across 10 districts. The selected districts were categorised into high and low latitudes by applying a cut-off point at latitude 31.5⁰N. We evaluated the physical parameters, SES, circulating FSH, and growth hormone (GH) levels in pre-menarche girls (N = 252) at different latitudes. Results: Self-reported age at menarche of girls residing at different latitudes in Pakistan showed that higher latitude is associated with delayed age at menarche. Higher latitude was associated with reduced circulating FSH levels, as well as lower parameters of physical growth including body mass index (BMI), waist-hip ratio and, waist-height ratio (all p < 0.05) in the pre-menarcheal girls. However, circulating GH levels were not affected by latitude. On the other hand, lower SES was associated with reduced GH levels and lower BMI, which are considered as probably the primary determinants of physical growth. Conclusions: Taken together, we show that higher latitude may delay the sexual maturation, while poor SES may delay the physical growth in girls.